2008
DOI: 10.1029/2008gl034536
|View full text |Cite
|
Sign up to set email alerts
|

Sea salt aerosol production and bromine release: Role of snow on sea ice

Abstract: [1] Snow lying on sea ice could be a potentially important source of sea salt aerosol, as small snow particles, rich in salts, can be easily lifted into the air though blowing-snow events. Using a measured distribution of snow salinity on Antarctic sea ice and a blowing snow sublimation parameterization, we derive a method for estimating sea salt aerosol production, and bromine release, during blowing-snow events. Compared with sea salt aerosol production rates from the open ocean, we find that the aerosol pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
464
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(483 citation statements)
references
References 28 publications
(38 reference statements)
16
464
2
1
Order By: Relevance
“…One possible explanation could be a dynamically driven bromine emission mechanism: low tropopause is frequently associated to low pressure cyclone systems and strong surface winds. Recent studies (Yang et al, 2008 andJones et al, 2009 and have provided convincing indications that the production of sea salt aerosol from snow lying on sea ice during blowing snow events (triggered by very strong surface winds) and the subsequent release of bromine, could be an important contribution to the bromine explosion phenomenon in the polar regions (Arctic and Antarctic). In order to investigate whether our analysis reflects this process assumed for bromine explosions, we have compared results of Fig.…”
Section: Polar Tropospheric Bromentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation could be a dynamically driven bromine emission mechanism: low tropopause is frequently associated to low pressure cyclone systems and strong surface winds. Recent studies (Yang et al, 2008 andJones et al, 2009 and have provided convincing indications that the production of sea salt aerosol from snow lying on sea ice during blowing snow events (triggered by very strong surface winds) and the subsequent release of bromine, could be an important contribution to the bromine explosion phenomenon in the polar regions (Arctic and Antarctic). In order to investigate whether our analysis reflects this process assumed for bromine explosions, we have compared results of Fig.…”
Section: Polar Tropospheric Bromentioning
confidence: 99%
“…However, the mechanism for the bromine release during bromine explosions is not completely understood. The surfaces needed for reactions can potentially come from frost flowers (Kaleschke et al, 2004), fresh sea ice (Frieß et al, 2004), sea salt aerosols (Vogt et al, 1996), sea salt deposits (McConnell et al, 1992) or sea salt aerosols produced during blowing snow events (Yang et al, 2008 andJones et al, 2009 and. In any case, the occurrence of such bromine emissions leads to efficient ozone depletion in the polar troposphere (e.g., Wennberg, 1999), as well as interactions with mercury chemistry (Schroeder et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the sea ice surface and snow cover provide major controls to the bromine (Br) and ozone (O 3 ) chemistry in the polar atmospheric boundary layer [Rankin et al, 2002;Kaleschke et al, 2004;Jones et al, 2006;Simpson et al, 2007;Yang et al, 2008;Nghiem et al, 2012], but mechanisms are not yet clear. The surface of first-year ice is generally more saline than that of multi-year ice, due to contributions from sea ice brine, flooding seawater and deposited sea salt from nearby leads and polynyas, while the surface of Arctic multi-year ice is washed by flushing in summer and is therefore almost fresh [e.g., Vancoppenolle et al, 2007].…”
Section: Sea Ice Surface Bromine and Tropospheric Ozone Chemistrymentioning
confidence: 99%
“…Surprisingly, a more extensive sea ice cover induces more sea salt recorded in Antarctic continental ice cores for present conditions [Iizuka et al, 2008], which is attributed to the highly saline frost flowers [Rankin et al, 2002] or to first-year, snow-covered sea ice. Snow lying on sea ice is a potentially important source of sea salt aerosol, as small snow particles, rich in salts, can be easily lifted into the air though blowingsnow events [Yang et al, 2008].…”
Section: Sea Ice Surface Bromine and Tropospheric Ozone Chemistrymentioning
confidence: 99%
“…Hence frostflower-originated aerosols contain a higher concentration of sea salt than aerosols originating from sea water. (Yang et al, 2008) also suggested the sublimation of salty blowing snow on sea ice as a potential unfractionated sea salt source. It is likely that different sea salt sources dominate and contribute to the sea salt records at different sites (Abram et al, 2011).…”
Section: Introductionmentioning
confidence: 99%